The Unlimited Rulebook: architecting the economy mechanics of games - Mizutani, Wilson Kazuo (2021)
The creative process of developing digital games alternates between modifying the game and playing it to evaluate the produced experience. However, the more technical effort is required to change the game, the longer it takes to evaluate it and the more expensive it becomes to change it. Our research focuses on a part of the creative process in games that is particularly prone to expensive technical changes: economy mechanics with self-amending rules. To minimize the cost of the changes they involve, we propose the Unlimited Rulebook, a reference architecture that guides developers when designing their game systems. We use a consolidated systematic process that traces each design decision back to the information sources that support it then evaluates the resulting reference architecture both qualitatively and empirically. The results show that, for the appropriate game genres and feature sets, the Unlimited Rulebook successfully avoids expensive retroactive changes by relying on extensibility, data-driven design, adaptive object models, and emulated predicate dispatching.